Berczeli Anzelm Károlyhoz - Fehér Tibor (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1938)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek